2005
DOI: 10.1038/modpathol.3800400
|View full text |Cite
|
Sign up to set email alerts
|

p16/INK4a gene methylation is a frequent finding in pulmonary MALT lymphomas at diagnosis

Abstract: p16/INK4a gene alterations have been associated with tumor progression in lymphoid malignancies. However, their significance in mucosa-associated lymphoid tissue (MALT) lymphoma is unclear. We investigated p16 gene methylation and mutation in a large series of untreated cases of pulmonary MALT lymphoma and diffuse large B-cell lymphoma (DLBL), and correlated p16 gene alterations with a MALT lymphoma-specific API2-MALT1 fusion and the clinicopathologic features of MALT lymphoma. The API2-MALT1 fusion was detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…Recently, p16 gene methylation was detected in 60% of MALT lymphoma cases, and it was also suggested that p16 methylation is not associated with tumor progression, but may be an early event in MALT lymphomagenesis. 49 In addition, mutations in the FAS gene were also found at a high frequency (60%) in MALT lymphoma. 50 FAS is a mediator of cell death in the germinal center B cells, which suggests that its inactivation may be involved in the pathogenesis of MALT lymphoma.…”
Section: Molecular Genetics Of Mucosa-associated Lymphoid Tissue Lympmentioning
confidence: 99%
“…Recently, p16 gene methylation was detected in 60% of MALT lymphoma cases, and it was also suggested that p16 methylation is not associated with tumor progression, but may be an early event in MALT lymphomagenesis. 49 In addition, mutations in the FAS gene were also found at a high frequency (60%) in MALT lymphoma. 50 FAS is a mediator of cell death in the germinal center B cells, which suggests that its inactivation may be involved in the pathogenesis of MALT lymphoma.…”
Section: Molecular Genetics Of Mucosa-associated Lymphoid Tissue Lympmentioning
confidence: 99%
“…[40][41][42] However, recent studies have shown that methylation of these genes may be an early event in lymphomagenesis: DAPK and p16 gene methylation is frequently found in premalignant and low-grade lymphoid disorders, not associated with tumor progression, and their methylation status is maintained in higher-grade or advanced lymphoid neoplasms. [43][44][45][46][47][48] In line with these findings, methylation of DAPK and p16 is a common, early epigenetic phenomenon that allows tumor cells to promote cellcycle progression and escape the normal apoptosis of a non-antigen-stimulated expanded B-cell population. Unlike base substitutions or gene deletions, changes in DNA methylation are potentially reversible.…”
Section: Primary Cutaneous Marginal Zone B-cell Lymphoma H Takino Et Almentioning
confidence: 89%
“…Methylation of a large number of genes has been described in virtually all types of cancers. MALT lymphomas show a high grade of p16/INK4a methylation [29][30][31][32]40,41], suggesting that inactivation of p16/INK4a by methylation may play an important role in the development of MALT lymphomas. In particular, it has been suggested that methylation of this gene is one of the early events in the development of lymphoid malignancies [42][43][44].…”
Section: Discussionmentioning
confidence: 99%